Early Mobilization Intervention Through Family Support for Post Laparotomy Wounds - Hanawati, Siti; Sulistyawati, Dwi; Suhariyanto, Suhariyanto; Ndeta, Egidius Umbu (Jurnal Keperawatan Priority, 2024)
Post laparotomy complications increase every year, ending in surgical wound infections. Efforts to prevent the healing process from taking a long time with early mobilization. So there is a need for a family support system.To determine the effect of early intervention through family support on the post-laparotomy wound healing process in the Intensive Care Unit (ICU). This research used a quasi-experiment with a pre-test and post-test without control, a time series approach. The sample of 13 respondents used Non-Probability Sampling, namely Purposive Sampling. The research was conducted from February to March at Hospital In the research phase, families were provided with early mobilization education with family support through educational books and applied to patients. Data analysis used the Wilcoxon test. The highest average family support was emotional support and appreciation with a mean of 13.23. Wound healing process after 5 days of observation, average increase in wound healing process pre 10.00 and post 10.15 There is an influence of early mobilization intervention through family support on the post laparotomy wound healing process in the Intensive Care Unit (ICU) of Hospital X with a p-value of 0.001 (< 0.05).